Swipe Left to Pray. Analyzing Authority and Transcendence in Prayer Apps - Karis, Tim (Entangled Religions, 2020)
This paper centers on a fairly new phenomenon in digital religion: prayer apps. After an overview of their typical features, the paper will present a number of analytical perspectives on such apps, arguing that investing in theoretical work is needed, particularly in a young research field. Starting points are provided by Heidi Campbell’s four-layer model of religious authority, Michel Foucault’s concept of “technologies of the self,” Birgit Meyer’s understanding of religion as a practice of mediation, and by the conceptualization of the transcendence/immanence distinction developed at the Käte Hamburger Kolleg Dynamics of the History of Religions Between Asia and Europe at the Center for Religious Studies, Ruhr-Universät Bochum. With regards to authority, it will be pointed out that prayer apps employ highly different strategies of authorization. These include the evocation of traditional authority, building trust through the use of familiar design language (often borrowed from outside the religious field), and self-imposed strategies aimed at the ‘improvement’ of the individual believer. As for the transcendence/immanence-distinction, it will be argued that it is important to differentiate between prayer apps that have a more auxiliary character, helping users to prepare their offline praying practice, and those apps that allow users to pray directly on their phone - which has significant implications for the understanding of transcendence.